A Genome-Scale Analysis of the PIN Gene Family Reveals Its Functions in Cotton Fiber Development - Zhang, Yuzhou; He, Peng; Yang, Zuoren; Huang, Gai; Wang, Limin; Pang, Chaoyou; Xiao, Hui; Zhao, Peng; Yu, Jianing; Xiao, Guanghui (Frontiers in Plant Science, 2017)
The PIN-FORMED (PIN) protein, the most important polar auxin transporter, plays a critical role in the distribution of auxin and controls multiple biological processes. However, characterizations and functions of this gene family have not been identified in cotton. Here, we identified the PIN family in Gossypium hirsutum, Gossypium arboreum, and Gossypium raimondii. This gene family was divided into seven subgroups. A chromosomal distribution analysis showed that GhPIN genes were evenly distributed in eight chromosomes and that the whole genome and dispersed duplications were the main duplication events for GhPIN expansion. qRT-PCR analysis showed a tissue-specific expression pattern for GhPIN. Likely due to the cis-element variations in their promoters, transcripts of PIN6 and PIN8 genes from the At (tetraploid genome orginated from G. arboreum) subgenome and PIN1a from the Dt (tetraploid genome orginated from G. raimondii) subgenome in G. hirsutum was significantly increased compared to the transcripts in the diploids. The differential regulation of these PIN genes after the polyploidization may be conducive to fiber initiation and elongation. Exogenously applied auxin polar transport inhibitor significantly suppressed fiber growth, which is consistent with the essential function of these PIN genes for regulating cotton fiber development. Furthermore, the overexpression of GhPIN1a_Dt, GhPIN6_At, and GhPIN8_At in Arabidopsis promoted the density and length of trichomes in leaves.